Pengembangan Media 3D (Smartbox : Petualangan di Dunia Rantai Kehidupan) Pada Materi Rantai Makanan - Illma Asfara; Andini Dwi Maulina; Dean Cahyani Akira (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2026)
This study aimed to develop a learning medium called 3D SmartBox: Adventure in the World of Food Chains for teaching food chain concepts to fifth-grade elementary school students. The research employed the Research and Development (R&D) method up to the initial product revision stage. Data were collected through interviews, media expert validation questionnaires, practicality questionnaires completed by one fifth-grade teacher, and response questionnaires completed by one fifth-grade student. The results showed that the SmartBox achieved a validity score of 87.7%, categorized as very valid, while the practicality scores from both the teacher and the student reached 96%, categorized as highly feasible. This learning medium was able to enhance students' motivation, active participation, and understanding of food chain concepts through concrete and visual learning experiences. However, some detachable components were found to be prone to coming loose during assembly and disassembly activities, indicating the need for improvements in materials and adhesive systems. Overall, the SmartBox is considered suitable for use as a science and social studies (IPAS) learning medium in elementary schools.